2005
DOI: 10.1007/s00431-004-1546-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of childhood obesity and obesity-related cardiovascular risk factors on glomerular and tubular protein excretion

Abstract: According to our results, clinically healthy obese children have a higher degree of albuminuria and beta-2-microglobulinuria than normal weight children, indicating early renal glomerular and tubular dysfunction as a consequence of childhood obesity. The urinary albumin/creatinine ratio in the obese children was associated with certain metabolic derangements linked to obesity, and also with the clustering of features of the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
2
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 36 publications
6
59
2
5
Order By: Relevance
“…In this context, adolescents with optimal and average KIDMED score compared with those with low score had higher values of body mass index and waist circumference, whereas exhibit lower ACR levels. Our findings are in contrary to studies based on data from obesity clinics in which ACR was found to be higher in obese children compared with normal weight children of the same age, underscoring the relation between obesity and albuminuria in pediatric population (Csernus et al, 2005;Burgert et al, 2006;Invitti et al, 2006). Nevertheless, in consistency with our results an analysis of the general adolescent population of the NHANES data showed that the prevalence of microalbuminuria was higher in non-obese teenagers and ACR was related with glucose metabolism dysregulation (Nguyen et al, 2008).…”
Section: Discussioncontrasting
confidence: 54%
“…In this context, adolescents with optimal and average KIDMED score compared with those with low score had higher values of body mass index and waist circumference, whereas exhibit lower ACR levels. Our findings are in contrary to studies based on data from obesity clinics in which ACR was found to be higher in obese children compared with normal weight children of the same age, underscoring the relation between obesity and albuminuria in pediatric population (Csernus et al, 2005;Burgert et al, 2006;Invitti et al, 2006). Nevertheless, in consistency with our results an analysis of the general adolescent population of the NHANES data showed that the prevalence of microalbuminuria was higher in non-obese teenagers and ACR was related with glucose metabolism dysregulation (Nguyen et al, 2008).…”
Section: Discussioncontrasting
confidence: 54%
“…Csernus et al (28) reported a positive association between proteinuria and adult obesity, consistent with the identification of obesity as an independent risk factor for proteinuria. However, in other studies, either proteinuria was not related to obesity (29) or obese children had higher albuminuria than the control group (28).…”
Section: Discussionsupporting
confidence: 53%
“…This condition is quite common in obese children and adolescents. Csernus et al showed elevated levels of albuminuria and β2-microglobulinuria in obese children versus normal weight children, suggesting early renal glomerular and tubular injury as a consequence of obesity in children [12]. Ferris et al demonstrated that microalbuminuria was strongly related to the severity of obesity in adults.…”
Section: Microalbuminuriamentioning
confidence: 99%